PLANTEAMIENTO DE MECANISMOS DE RETRIBUCIÓN POR SERVICIOS ECOSISTÉMICOS HÍDRICOS EN EL RÍO SAN LUCAS-CAJAMARCA-PERÚ. - Huamán, L.P. (2021)
The current inefficiency and water quality, in addition to the degradation of aquatic ecosystems led to the publication in 2017 of the Resolution of the Board of Directors No. 027-2019-SUNASS-CD (modifying the R.C.D. N°045-2017-SUNASS-CD) that establishes the Mechanisms of Remuneration for Ecosystem Water Services in Peru, in order to find solutions. The purpose of the work is to propose sustainable mechanisms and evaluate their possible implementation in the San Lucas river - Cajamarca which in its course supplies drinking water to 30% of the population. To achieve this, the Guide for the "Base Water Diagnosis" Applied to Sanitation Service Providers in Peru was applied, making a baseline of the river. As a result, the river was found to be potentially erosive and slightly steep, with frequent rainy seasons between January and April, and its main land use is agriculture. In order to evaluate it, the social perception was obtained through interviews with taxpayers and retributors. Among the taxpaying population, 65.38% approve of the planting and harvesting of water and 19.23% approve of the improvement of irrigation techniques. In addition, 92.31% of the taxpaying population is in favor of paying for the implementation of mechanisms to ensure water supply for their consumption. Likewise, in correlation with the prioritization matrix, it is concluded that the implementation of both water mechanisms in the San Lucas River is socially and technically feasible. Suggesting the implementation of these two mechanisms in order to sustainable use of water resources of the San Lucas River to demonstrate the improvement of quality of life in the short term. © 2021 Latin American and Caribbean Consortium of Engineering Institutions.